A Multi‐functional Biofilm Used as an Active Insert in Modified Atmosphere Packaging for Fresh Produce. (December 2015) - Wang, Hong Jiang; An, Duck Soon; Rhim, Jong‐Whan; Lee, Dong Sun
Abstract : We developed a multi‐functional agar‐based biofilm for fresh produce packaging by modulating its CO2 absorption and water vapour absorption functions. The film was prepared from solutions containing agar as a matrix and a water vapour absorbent, glycerol as a plasticizer, and sodium carbonate (SC) and/or sodium glycinate (SG) as a CO2 absorbent. The optical, mechanical, and CO2 and water vapour absorption properties of SC, SG, and SC/SG films were investigated. Multi‐functional films tended to show poor mechanical properties, with a hard texture and an opaque and yellowish colour. The three films had different CO2 absorption capacities and coefficients, with SC film showing the highest absorption, followed by SC/SG and SG films. The water absorption coefficients were much higher than those of CO2, with the opposite dependence on the absorbent compound. The multi‐functional benefits of the developed film were shown by using the film for modified atmosphere packaging (MAP) of shiitake mushrooms as an insert label. A tailored MAP design for shiitake mushrooms was produced based on mass transfer mathematical models. The package attached with SC film label was capable of generating the desired internal atmosphere and thus showed the best quality preservation in terms of colour, firmness, flavour score, and bacterial growth after 5‐day storage. A tailored MAP system with our multi‐functional film can provide an optimal modified atmosphere for CO2 ‐sensitive fresh commodities, preserve their quality, and extend their shelf life. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A multifunctional agar‐based biofilm modulated in its CO2 absorption and water vapor absorption functions was developed for fresh produce packaging. The film was prepared from solutions containing agar as a matrix and a water vapor absorbent, glycerol as a plasticizer, and sodium carbonate and/or sodium glycinate as a CO2 absorbent. The multifunctional benefits of the developed film were shown by using the film for modified atmosphere packaging of shiitake mushrooms as an insert label.